New advances in biological preservation technology for aquatic products - Xiaobao Nie; Zhijie Zuo; Ruichang Zhang; Si Luo; Yongzhou Chi; Xiangyang Yuan; Chengwen Song; Yongjiang Wu (npj Science of Food)
Abstract Aquatic products, characterized by their high moisture content, abundant nutrients, and neutral pH, create an optimal environment for the rapid proliferation of spoilage organisms, lipid oxidation, and autolytic degradation. These factors collectively expedite the spoilage and deterioration of aquatic products during storage and transportation within the supply chain. To maintain the quality and extend the shelf-life of aquatic products, appropriate preservation methods must be implemented. The growing consumer preference for bio-preservatives, is primarily driven by consumer demands for naturalness and concerns about environmental sustainability. The present review discusses commonly employed bio-preservatives derived from plants, animals, and microorganisms and their utilization in the preservation of aquatic products. Moreover, the preservation mechanisms of bio-preservatives, including antioxidant activity, inhibition of spoilage bacteria and enzyme activity, and the formation of protective films are reviewed. Integration of bio-preservation techniques with other methods, such as nanotechnology, ozone technology, and coating technology that enhance the fresh-keeping effect are discussed. Importantly, the principal issues in the application of bio-preservation technology for aquatic products and their countermeasures are presented. Further studies and the identification of new bio-preservatives that preserve the safety and quality of aquatic products should continue.